APPROACHES TO ARTIFICIAL INTELLIGENCE IN THE CONTEXT OF AUTISTIC SPECTRUM DISORDER - Celentano, Stella Prado; Gibertoni, Daniela (Revista Interface Tecnológica, 2022)
Seeking to analyze and understand the types of artificial intelligence approaches in the context of autism spectrum disorder, the present research was designed to gather and understand how other researchers around the world apply technology in their work and with this it will be possible to answer relevant questions about the use of AI related to autism and how it can be valuable for this branch of healthcare, as well as understanding how devices are being developed and tested in patients, how promising and assertive these devices are and what are the main challenges encountered along the way . This study used the systematic mapping of the literature as a research methodology. The results found through the analysis of the selected works supported relevant conclusions about the questions mentioned above, one of them being the fact that the use of devices based on artificial intelligence obtained motivating results, being able to optimize the communication between student and teacher, as well as to quickly and accurately detect the presence or absence of autism spectrum disorder in patients who participated in clinical trials, thus enabling early intervention and treatment.
Keywords: artificial intelligence; machine learning; autism